Aesthetics of absence texts on theatre - Goebbels, Heiner 1952- (Routledge, 2015)
Zusammenfassung: "Aesthetics of Absence presents a significant challenge to the many embedded assumptions and hierarchical structures that have become 'naturalised' in western theatre production. This is the first English translation by Heiner Goebbels, the renowned German theatre director, composer and teacher. These writings map Heiner Goebbels' engagement with 'Aesthetics of Absence' through his own experience at the forefront of innovative music-theatre and performance making. In this volume Goebbels reflects on works created over a period of more than twenty years staged throughout the world; introduces some of his key artistic influences, including Robert Wilson and Jean-Luc Godard; discusses the work of his students and ex students the collective Rimini Protokoll, and, sets out the case for a radical re thinking of theatre and performance education. He gives us a rare insight into the rehearsal process of critically acclaimed works such as Eraritjaritjaka and Stifters' Dinge explaining, in meticulous detail, the way he weaves an eclectic range of references from fine art, theatre, literature, politics, anthropology, contemporary and classical music, jazz and folk, into his multi- textured music-theatre compositions. As an artist who is prepared to share his research and demystify the processes through which his own works come into being, as a teacher with a coherent pedagogical strategy for educating the next generation of theatre makers, in this volume, Goebbels brings together practice, research and scholarship"--(Provided by publisher.)
Lizenz des Verlag Theater der Zeit, Berlin
Keywords: 2000-2099; Theater--Germany--History--21st century.; Theater.; Germany.; History.; Theater; Theaterpädagogik; Tyskland.; Aufsatzsammlung